PENGARUH STRUKTUR ASET, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, PROFITABILITAS, RISIKO BISNIS, DIVIDEN DAN DEGREE OF OPERATING LEVERAGE TERHADAP STRUKTUR KEUANGAN - NITA ASTUTI; STELLA STELLA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The purpose of this research is to test and analyze empirically the influence of tangibility, sales growth, firm size, profitability, business risk, dividend and degree operating leverage toward financial structure. Sample of this research is food and beverages companies that listed in Indonesia Stock Exchange for period 2003-2012. The purposive sampling is used as sampling technique. This result of this research shows that tangibility, sales growth, firm size, profitability, business risk, dividend and degree operating leverage do not influence the financial structure.